Best Supportive Care Versus Whole-Brain Irradiation, Chemotherapy Alone, or WBRT Plus Chemotherapy in Patients With Brain Metastases From Small-Cell Lung Cancer: A Case-Controlled Analysis - Li, Hongwei; Xue, Ruiqi; Yang, Xiaotang; Han, Songye; Yang, Weihua; Song, Xin; Zhang, Xiaqin; Cao, Jianzhong; Jia, Sufang; Wang, Weili; Lian, Jianhong (Frontiers in Oncology, 2021)
Background: Whole-brain irradiation (WBRT) and systemic chemotherapy are the mainstay treatments for small-cell lung cancer (SCLC) brain metastases (BM). However, current recommendations are mainly based on evidence from retrospective analyses. A recent randomized trial found no benefits from WBRT compared with best supportive care (BSC) in patients with more than three BM from non-small-cell lung cancer (NSCLC). Herein, we aimed to evaluate the roles of WBRT and chemotherapy further in the management of BM from SCLC. Materials and Methods: There were 698 patients with BM from SCLC included. Of these, 580 received intensive treatment (Group 1), including 178 who received WBRT only (Group 1a), 129 who received chemotherapy only (Group 1b), and 273 who received WBRT plus chemotherapy (Group 1c). The other 118 received BSC (Group 2). Propensity score matching (PSM) analysis was used to compare Group 2 with each of the other groups. Results: After PSM, compared with Group 2, patients in Group 1 had a prolonged overall survival in both univariate and multivariate tests, with a median survival time of 10 months (95% CI = 911) in Group 1 and 3.5 months (95% CI = 27) in Group 2 (p < 0.001). In subgroup analyses, patients who received WBRT plus chemotherapy were more likely to benefit from treatment (p < 0.001). Chemotherapy alone or WBRT alone did not show survival benefits. Conclusion: WBRT plus chemotherapy improved OS in patients with BM from SCLC as compared to BSC. Chemotherapy alone and WBRT alone did not show survival benefits. Our findings suggest that SCLC patients with BM who receive WBRT combined with chemotherapy have a better outcome than those receiving BSC alone.